FEATURES RADIATION FIELD IN NATURAL AND ARTIFICIAL UNDERGROUND CAVITIES: (according to observations in Мozrov and Аrji caves) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Radiation field in natural and artificial underground voids is presented in the work. Based on field studies, carried out in Mozrov and Arji caves, it was revealed the intensity of radiation field in these voids is lesser than in ambient conditions because of absence of $γ$-ray radiation there, which are penetrate into atmosphere from ionosphere. This should be taken into account during the operation of the indoor premises, selecting tourist trips, and construction works.
Keywords: caves; radiation field; ionosphere; intensity; studies; structure; tourist trips